(untitled) (Journal of Misan Researches, 2021)
The world and its inhabitants were on a date with the spread of a new deadly epidemic (Coved 19), disrupting life in all its joints and fields and imposing a preventive home ban on all, except for some sensitive, important and necessary areas of life (security - food - health), thus disrupting the most important joints of building and preparing individuals for life and its corner The only president who is detailed education. In order to ensure that this field is not completely disrupted and in the upper stages of it at the very least, those responsible for education and their operations, whether at the level of families or governments, have begun to resort to e-learning in providing services and practices of that process, and despite its disadvantages and disadvantages, it is the available alternative At the present time, the most important disadvantage of this education is the absence of the human element from it, as the realistic presence of both sides of the class communication process (teacher - learner) It achieves enormous benefits, linked to a set of dimensions, the most important of which are the human and social dimensions, which entail many internal and external benefits for the teaching and learning processes. They affect the achievement of learners and the modification of their behaviors, and contribute to developing their awareness of the problems that affect their lives and their future; Research procedures will reveal the effects of the absence of these two dimensions from the students’ point of view.